1990
DOI: 10.1530/acta.0.1220283
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum thyroid dysfunction in Bangkok: A geographical variation in the prevalence

Abstract: To determine the prevalence of thyroid dysfunction in Thai postpartum women, we evaluated thyroid function and thyroid autoantibodies in 812 consecutive unselected women at 1.5 months post partum. At 3.5 months post partum 570 women without previous thyroid abnormality returned for a second set of thyroid function test. The prevalence of thyroid dysfunction was 1.1%, which was less than that reported from other countries. Various types of postpartum thyroid dysfunction, namely, transient thyrotoxicosis followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…The rate of PPT in countries with iodine de®ciency has been reported to be low (6). It is conceivable that an increase in PPT, such as that reported for thyrotoxicosis, may have occurred in Tehranian women following consumption of iodized salt used to control iodine-de®ciency disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of PPT in countries with iodine de®ciency has been reported to be low (6). It is conceivable that an increase in PPT, such as that reported for thyrotoxicosis, may have occurred in Tehranian women following consumption of iodized salt used to control iodine-de®ciency disorders.…”
Section: Discussionmentioning
confidence: 99%
“…120 Significant differences in prevalence between ethnic groups have been reported. 121 Results from genetic studies of the HLA region in PPT have been conflicting. 122,123 As the CTLA4 polymorphisms associate with AITD, CTLA4 are considered a putative candidate gene in PPT.…”
Section: Postpartum Thyroiditis (Ppt)mentioning
confidence: 99%
“…Most patients have normal thyroid function at one year [10], and all three episodes in the present case recovered within one year. Abortion is a common clinical problem, and several studies have revealed a strong correlation between presence of thyroid antibodies and spontaneous abortion [11][12][13]. Bagis et al [3] reported that 50% of thyroid autoantibody-positive women and 14.1% of thyroid autoantibody-negative patients had a history of spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%